Participant perceptions of the faculty development Educational Research Series - Dalgarno, Nancy; Laverty, Corinne; Egan, Rylan; Garton, Kendall; Soleas, Eleftherios; Babando, Jordan; van Wylick, Richard (Teaching and Learning Inquiry, 2020)
Interest in the Scholarship of Teaching and Learning (SoTL) is driven in part by the need to provide systematic academic development for faculty anchored in evidence-based practice such as the introduction of quality assurance frameworks. This article reports on a mixed-method evaluation of one institution’s grassroots multidisciplinary faculty development program, called the Educational Research Series, to determine if it met the needs of its faculty, graduate student, and staff participants. Conducted at one mid-sized university in southern Ontario and framed, as was the program design and implementation, by both adult learning theory and constructivism, the evaluation collected data from session exit surveys, attendee interviews, and facilitator focus groups. The data analysis revealed that reasons for participating included increasing levels of understanding, receiving individual support, and learning about colleagues’ research interests. The major strengths of the program included individual learning, resources, facilitator expertise, interactive sessions, and the multidisciplinary focus. The main challenges centered on depth versus breadth of the sessions, time, and educational language and theory. Participants recommended additional resources, communication among facilitators, institutional recognition, and increased depth of content. As a result of this evaluation, an Advanced Educational Research Series is being offered at the institution. This article will inform other institutions wishing to build SoTL as a field within their institutions.